Evaluating the structural priorities for the seismic vulnerability of civilian and industrial wastewater treatment plants. (August 2017) - Panico, A.; Basco, A.; Lanzano, G.; Pirozzi, F.; Santucci de Magistris, F.; Fabbrocino, G.; Salzano, E.
Highlights: Seismic vulnerability of municipal or industrial wastewater treatment plants is needed. New vulnerability functions based on damage observation of available earthquake reports. Risk states based on loss of waste to the environment are given (NaTech). Municipal WTTPs are more vulnerable to earthquakes with respect to the industrial systems. Non-structural components (sedimentation basins and digesters) are less resilient. Abstract: Wastewater disposal systems are complex systems composed by several interconnected elements. In the aftermath of dramatic natural events, such as the earthquake, the failure of any of these elements can result in the deterioration of the environment as well as in the risk for the exposed population, due to leakage of untreated or un-properly treated wastewater on soil and/or its discharge into superficial waters. This paper presents a multi-disciplinary methodology for the evaluation of the seismic vulnerability of municipal or industrial wastewater treatment plants, based on damage observation of available earthquake reports. Specific fragility curves and threshold values expressed in terms of Peak Ground Acceleration (PGA) are presented and compared with existing functions. The methodology fully comply requirements of most relevant and effective risk analysis tools or for land-use planning and can be adopted for the definition of structural priorities of plants.